2015
DOI: 10.3329/bmrcb.v40i3.25231
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B27 antigen frequency among suspected Spondyloarthropathy patients attaining a tertiary level hospital of Bangladesh

Abstract: Human leukocyte antigen B27 (HLA-B27), a class I molecules of the major histocompatibility complex has a strong disease association with different types of spondarthropathies (SpA). The strength of this disease association varies markedly among racial and ethnic populations. The present study aimed to identify the HLA-B27 antigen frequencies among suspected SpA patients as well as healthy Bangladeshi individuals. The frequency of HLA-B27 was determined in 1500 patients and 1000 healthy subjects attending the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…The mean AS prevalence per 10,000 is estimated to be 23.8 in Europe. However, it is substantially lower in the Japanese population (0.7), consistent with the lower frequency of HLA-B27 in the Japanese general population (0.5% or less), compared with Europeans (4-13%) and other Asian populations such as the Chinese (4-8%) or South Koreans (2.3-3%) [5][6][7][8][9].…”
Section: Introductionsupporting
confidence: 53%
“…The mean AS prevalence per 10,000 is estimated to be 23.8 in Europe. However, it is substantially lower in the Japanese population (0.7), consistent with the lower frequency of HLA-B27 in the Japanese general population (0.5% or less), compared with Europeans (4-13%) and other Asian populations such as the Chinese (4-8%) or South Koreans (2.3-3%) [5][6][7][8][9].…”
Section: Introductionsupporting
confidence: 53%
“…22,23 The specific genetic marker HLA-B27 was positive in 54% of Spondyloarthritis patients, with a men predominance. In a study conducted by Umamaheshwari et al, involving 50 patients, 26% of cases were found to be HLA-B27 positive, 24 while in other studies by Mishra MN et al, 25 and Nessa et al, 26 the frequency of HLA-B27 antigen among SpA patients were 56% and 49.2% respectively with our study.…”
Section: Discussionsupporting
confidence: 53%
“…With a predominance of men, 54% of patients with spondyloarthritis tested positive for the particular genetic marker HLA-B27. HLA-B27 positivity was noticed in 26% of the 50 patients studied by Uma Maheshwari et al, 36 while additional investigations of Mishra MN et al 37 and Nessa et al 38 indicated that HLA-B27 antigen was present in 49.2% and 56% of SpA patients, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…Comparing men and women with SpA patients, it was observed that more males (64%) than women (36%) had HLA-B27 positivity, which is consistent with other research findings. 36,38 However, Vaidya et al 3 stated that there was no significant difference was noticed in HLA-B27 incidence between women and men, and it was found that the illness was more common in the male population.…”
Section: Discussionmentioning
confidence: 99%